Screen-space VPL propagation for real-time indirect lighting - Aranha, Vitor M.; Macedo, Marcio; Apolinário Jr., Antônio (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2020)
Reproducing indirect lighting in real time for 3D scenes is a computationally intensive task, but its results add realism and visual fidelity to game-like scenarios and applications. Previous attempts to solve this task explored the use of paraboloid shadow maps for hemispherical visibility queries and Virtual Point Lights (VPLs) for light transport simulations. In our work we aimed at reproducing up to two diffuse bounces of light, while maintaining real-time framerates. We propose an extension to clusterization-based methods in order to sample less VPLs per paraboloid shadow map and capture more bounces of light efficiently. We also propose a projection-aware sampling method to improve sampling efficiency. Our experiments show that, with our approach, it is possible to generate two-bounce VPLs in real time even for low-end commodity GPUs, providing a fast method for indirect illumination.